2018
DOI: 10.5897/ajb2017.16289
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen-fixing Frankia significantly increases growth, uprooting resistance and root tensile strength of Alnus formosana

Abstract: Restoration of Alnus formosana (Burk.) Makino on landslide areas is important for agroforestry, forestry and soil erosion control in Taiwan. To ensure successful reforestation, A. formosana seedlings have to develop strong root system for nutrient and water acquisition as well as anchorage. Inoculating of A. formosana with symbiotic nitrogen-fixing actinobacteria Frankia may help mitigate drought and nutrient deficiencies on landslide sites. However, the effects of Frankia inoculation on growth, root architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They are important nitrogen suppliers in terrestrial ecosystems, so they have a wide application prospect in agriculture and forestry. Thus, Frankia has the potential to be used in nature as a powerful resource 25 . Other studies have found that Frankia , like other actinomycetes, can produce antimicrobial substances that inhibit the growth of microorganisms, such as Escherichia coli , Staphylococcus aureus , Candida albicans , and Penicillium chrysogenum 26 .…”
Section: Introductionmentioning
confidence: 99%
“…They are important nitrogen suppliers in terrestrial ecosystems, so they have a wide application prospect in agriculture and forestry. Thus, Frankia has the potential to be used in nature as a powerful resource 25 . Other studies have found that Frankia , like other actinomycetes, can produce antimicrobial substances that inhibit the growth of microorganisms, such as Escherichia coli , Staphylococcus aureus , Candida albicans , and Penicillium chrysogenum 26 .…”
Section: Introductionmentioning
confidence: 99%